2013
DOI: 10.1371/journal.pone.0071063
|View full text |Cite
|
Sign up to set email alerts
|

Working Memory Updating Function Training Influenced Brain Activity

Abstract: Recent studies demonstrated that working memory could be improved by training. We recruited healthy adult participants and used adaptive running working memory training tasks with a double-blind design, combined with the event-related potentials (ERPs) approach, to explore the influence of updating function training on brain activity. Participants in the training group underwent training for 20 days. Compared with the control group, the training group's accuracy (ACC) in the two-back working memory task had no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
65
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(72 citation statements)
references
References 39 publications
5
65
1
1
Order By: Relevance
“…The functional significance of P3 amplitude in working memory tasks is not yet fully understood. Some authors have suggested that P3 amplitude reflects the process of classifying task-relevant stimuli [ 45 ] whereas others have suggested that it reflects the updating of current information in working memory [ 46 , 49 , 74 ]. In particular, Kim et al [ 75 ] proposed that a larger P3 amplitude and shorter P3 latency in response to congruent stimuli than in response to incongruent stimuli on the n -back task is indicative of the updating of information or of the decision-making process.…”
Section: Discussionmentioning
confidence: 99%
“…The functional significance of P3 amplitude in working memory tasks is not yet fully understood. Some authors have suggested that P3 amplitude reflects the process of classifying task-relevant stimuli [ 45 ] whereas others have suggested that it reflects the updating of current information in working memory [ 46 , 49 , 74 ]. In particular, Kim et al [ 75 ] proposed that a larger P3 amplitude and shorter P3 latency in response to congruent stimuli than in response to incongruent stimuli on the n -back task is indicative of the updating of information or of the decision-making process.…”
Section: Discussionmentioning
confidence: 99%
“…Although this study documented functional brain differences related to family income at around age 14, there is considerable evidence that substantial brain plasticity occurs at this and older ages. Training on WM and other executive functions, such as selective attention, alters performance, evoked brain activation, the connectivity of intrinsic brain networks and white matter pathways, and the timing of brain responses as measured with event‐related potentials across as little as 4 to 5 weeks of training (Kundu, Sutterer, Emrich & Postle, ; Olesen, Westerberg & Klingberg, ; Takeuchi, Sekiguchi, Taki, Yokoyama, Yomogida et al ., ; Takeuchi, Taki, Nouchi, Hashizume, Sekiguchi et al ., ; Westerberg & Klingberg, ; Zhao, Zhou & Fu, ) and even across two sessions with direct neural feedback in the scanner (Zhang, Yao, Zhang, Long & Zhao, ).…”
Section: Discussionmentioning
confidence: 99%
“…The fronto-central P200 occurs with a latency around 200 ms, and is proposed to reflect processes involved in selective attention (Hillyard, Hink, Schwent, & Picton, 1973), executive attention ( Zhao, Zhou, & Fu, 2013) , stimulus classification ( GarcĂ­a-Larrea, Lukaszewicz, & MauguiĂ©re, 1992), STS (Dunn, Dunn, Languis, & Andrews, 1998) and intelligence (Lijffijt et al, 2009). The P300 component elicited at approximately 300ms post-stimulus by WM tasks ( e. g. , n-back) is proposed to index brain activities underlying fundamental attention, context updating and cognitive control processes ( Scharinger, Soutschek, Schubert, & Gerjets, 2017;Sumich et al, 2008;Polich, 2007;Watter, Geffen, & Geffen, 2001).…”
Section: Introductionmentioning
confidence: 99%